CORPUS LINGUISTICS RESEARCH: ANALYZING THE USE OF THE DEGREE OF COMPARISON IN WESTERN SONG - Dini Nurlailla Fadillah; Lilia Indriani (Faculty of Education and Teachers Training, 2021)
AbstractThe degree of comparison is either of the studies of grammar. It is a part of the subjects in corpus linguistics. The degree of comparison is a grammar term to denote a comparison. In comparing degrees of adjectives or adverbs, the form changes according to the level of comparison. The research is analyzing the use of the degree of comparison in western songs. The western song is very well-known in many, especially those with teenagers. New, several applications using western songs for blending. Initial positive and age-appropriate experiences with music have a considerable effect on English Foreign language learning, including pronunciation, vocabulary, comprehension, and expression. The research goal is to find the degree of comparison in western songs to help learn English for EFL. This research utilizes the descriptive qualitative method there is data collection to convey the result.